Urgensi Adopsi Mekanisme Non-Conviction Based Asset Forfeiture di Indonesia: Studi Komparatif dengan Sistem Perampasan Aset di Perancis - Anna Shania de Zeta Sinaga; Slamet Tri Wahyudi (Lembaga Yasin AlSys, 2026)
The development of contemporary criminal law shows a paradigm shift from a retributive approach toward a restorative-economic approach that emphasizes the recovery of state economic losses. As a state governed by law, as mandated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, Indonesia has a constitutional responsibility to uphold justice for the people’s economic rights through the strengthening of clean and transparent asset forfeiture instruments. This study aims to analyze the ratio legis of asset recovery in Indonesian criminal law regulations and to formulate the urgency of strengthening asset forfeiture mechanisms from the perspective of ius constituendum. This study used a normative juridical method with a statutory approach, a conceptual approach, and a comparative approach. The results show that the ratio legis of asset recovery in Law Number 31 of 1999 and Law Number 8 of 2010 remains conventional and is highly dependent on proof of personal wrongdoing (in personam), so it has the potential to encounter obstacles when the perpetrator dies or flees. Therefore, the adoption of the Non-Conviction-Based Asset Forfeiture mechanism in the Asset Forfeiture Bill is needed as a lex specialis by considering the success of the confiscation sans condamnation system and the professionalism of the AGRASC institution in France to improve the effectiveness of holistic state asset recovery. The conclusion of this study emphasizes the importance of theoretical reconstruction through the integration of civil and criminal law elements into an autonomous hybrid asset forfeiture regime, so that the direction of criminal law enforcement in Indonesia focuses not only on pursuing perpetrators but also on independently dismantling the financial power base derived from crime.